Photocatalysis by TiO₂ films at structure relaxation - Dmytrenko, O.P.; Kulish, N.P.; Busko, T.O.; Stashchuk, V.S.; Eremenko, A.M.; Smirnova, N.P.; Vityuk, N.V. (Functional Materials, 2007)
The crystalline and electron structure of TiO₂ and TiO₂/ZrO₂/SiO₂ coating obtained by sol-gel technique and annealed at 773 K and 873 K has been studied. The film synthesis and further heat treatment result in formation of nano-sized anatase particles with a developed surface and shallow and deep traps within the band gap of titania. Rater localized electron states correspond to these defects, which result in occurrence of some new optical absorption bands. Some of the optical conductivity bands belong to oxygen vacancies which are deep defects, and the other ones are connected with surface defects. The nature of surface defects should be various. The presence of shallow defects deforms the edge of conductive band, tailing it.